Penguatan Kepedulian Lingkungan dan Literasi Anak Pesisir: Program Edukasi Partisipatif di RT 05 Pantai Amal Kota Tarakan - Nurul Hidayat; Rizha Nurul Hidayah; Veronika Jonathan; Dewi Astina; Elisabet Sari Ona Deran; Nadiah, Nadiah; Alif Fathin Bimanta; Muhammad Rafie Maula; Edowardus (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This community service program aims to strengthen environmental awareness and literacy among coastal children through a participatory educational approach in RT 05 Pantai Amal, Tarakan City. The program involved children aged 6–12 years who participated in a series of integrated activities combining environmental education and literacy-based learning. Visual media, interactive discussions, and picture storybooks with environmental themes were used to create a learning process that was close to the children’s daily experiences. Observational data showed a significant increase in children’s understanding of coastal environmental conditions, their awareness of waste issues, and their willingness to engage in pro-environmental behavior. At the same time, literacy activities encouraged greater interest in reading, improved confidence in expressing ideas, and enhanced participation in group discussions. The integration of environmental awareness and literacy proved effective in shaping positive character traits, including responsibility, social awareness, and critical thinking. These findings indicate that participatory, context-based education can serve as an effective strategy for empowering coastal children and fostering sustainable values from an early age.